New ‘multi-omics’ approach and its contribution to hepatocellular carcinoma in China - Inagaki, Yoshinori; Song, Peipei; Kokudo, Norihiro; Tang, Wei (Chinese Journal of Cancer Research; Vol 26, No 6 (December 30, 2014): Chinese Journal of Cancer Research, 2014)
Hepatocellular carcinoma (HCC) is one of the most common liver neoplasms worldwide, and 70-80% cases are accounted in Asian countries (1). Etiological background of HCC patients is different in each country or area. In China, infection of hepatitis B virus (HBV) is a main etiological factor of increased incidence of HCC. In fact, 93 million HBV carriers are Chinese, accounting for 2/3 of such patients worldwide, and about 20 million of these people have chronic HBV infection (2). Chronic HBV infection is a high risk factor for development of HCC. Therefore, the follow-up of those chronic viral hepatitis type B patients and the early-detection of HCC in those patients are pressing tasks to reduce the incidence of HCC in China (3).